Dexmedetomidine modulates neuronal activity of horizontal limbs of diagonal band via α2 adrenergic receptor in mice - Xia-wei Zhang; Lei Chen; Chang-feng Chen; Juan Cheng; Ping-ping Zhang; Lie-cheng Wang (BMC Anesthesiology, 2023)
Abstract Background and objectives Dexmedetomidine (DEX) is widely used in clinical sedation which has little effect on cardiopulmonary inhibition, however the mechanism remains to be elucidated. The basal forebrain (BF) is a key nucleus that controls sleep-wake cycle. The horizontal limbs of diagonal bundle (HDB) is one subregions of the BF. The purpose of this study was to examine whether the possible mechanism of DEX is through the α2 adrenergic receptor of BF (HDB). Methods In this study, we investigated the effects of DEX on the BF (HDB) by using whole cell patch clamp recordings. The threshold stimulus intensity, the inter-spike-intervals (ISIs) and the frequency of action potential firing in the BF (HDB) neurons were recorded by application of DEX (2 µM) and co-application of a α2 adrenergic receptor antagonist phentolamine (PHEN) (10 µM). Results DEX (2 µM) increased the threshold stimulus intensity, inhibited the frequency of action potential firing and enlarged the inter-spike-interval (ISI) in the BF (HDB) neurons. These effects were reversed by co-application of PHEN (10 µM). Conclusion Taken together, our findings revealed DEX decreased the discharge activity of BF (HDB) neuron via α2 adrenergic receptors.